Online learning tool on external financing needs - KUSNADI, Yuanto (Institutional Knowledge at Singapore Management University, 2018)
In collaboration with colleagues at the Centre ofTeaching Excellence (CTE), I have developed an innovative online learningobject on External Financing Needs. This tool is designed to introduce a noveland refreshing way in teaching accounting and finance concepts to students andto create a more interactive learning experience in the classroom. The online learning tool is used in the two courses:Accounting for Entrepreneurs and Financial Management, to explain the relevantconcepts related to financial forecasting and financial planning. One unique feature about the learning object is that itprovides instantaneousfeedback to students as they can learn whether the numbers theyprovide are correct/wrong (as indicated bythe green/red font in the screen). In general,most of the students enjoyed learning about and using the tool and some of themwant more of something like this for their self-practice. In particular, theimmediate feedback feature that students received was regarded as the most useful feature, especiallyto the weaker students.